Spiritual Maturity and the Appropriate Age for a Bishop in Auxentius of Durostorum - Tone, Hiroshi (Scrinium, 2021)
Epistula de Wulfila episcopo by Auxentius of Durostorum reported that Ulfila became a bishop when he was thirty years old. This report was dramatized in order to emphasize Ulfila’s sanctity. This study will examine the symbolic meaning of thirty years old, and explain how it is a deep-rooted and continual idea in the arrangement of clerical offices. As a result, I contend that the symbolism of “thirty years old” was the appropriate age for someone to lead the community. This idea came from Numbers 4:2–3 and could be also found in the Judaic tradition. One could argue that this idea on spiritual leadership prevailed, was accepted and was later the basis of the clerical offices.